UMPSA excels in research, driving Advanced TVET - Mimi Sakinah, Abdul Munaim (UMPSA, 2024)
PEKAN, 9 October 2024 - Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), now celebrating 22 years, continues to gain international recognition by advancing research in sustainable development and green technology, while also strengthening Advanced Technical and Vocational Education and Training (TVET), known as Advanced TVET.